PECULIARITIES OF DIPLOMATIC VOCABULARY AND ITS TRANSLATION (KONFERENSIYA, 2025)
The paper considers about the characteristics of the diplomatic termsand diplomatic language in general. The relevance of this research is due to the needto study diplomatic terms present in the political texts and sources as a special objectof translation activity. The article offers some examples of diplomatic notions andtheir equivalents in Russian